2016
DOI: 10.1002/mats.201500072
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Computational and Experimental Study of Copolymerization Propagation Kinetics for 1-Ethylcyclopentyl methacrylate and Methyl methacrylate

Abstract: The crosspropagation of 1-ethylcyclopentyl methacrylate (ECPMA) and methyl methacrylate (MMA) has been studied using a combination of quantum chemistry calculations and experiment. Our computational work utilizes a trimer-to-tetramer reaction model, coupled with an ONIOM (B3LYP/6-31G(2df,p): B3LYP/6-31G(d)) method for geometry optimization and an M06-2X/6-311+G(2df,p) method plus SMD solvation model for single point energy calculations. The results show several trends: the identity of the ultimate unit of a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…This is true for simple systems like MMA/DMA, 4 but also for xMA bearing diverse functional groups in their ester side chains such as 2-(2-bromopropionyloxy) propyl methacrylate, 49 AAEMA, 37 or 1-ethylcyclopentyl methacrylate. 50 Furthermore, a variety of xMA/n-alkyl acrylate (xA) pairs consistently produce methacrylate-rich copolymers. 2,3,7,51 For such xMA/xMA and xMA/xA copolymerization systems, it is found that the effect of solvent choice on copolymer composition is small as long as the difference in monomer and solvent polarities is not large.…”
Section: Homopropagation Rate Coefficientsmentioning
confidence: 99%
“…This is true for simple systems like MMA/DMA, 4 but also for xMA bearing diverse functional groups in their ester side chains such as 2-(2-bromopropionyloxy) propyl methacrylate, 49 AAEMA, 37 or 1-ethylcyclopentyl methacrylate. 50 Furthermore, a variety of xMA/n-alkyl acrylate (xA) pairs consistently produce methacrylate-rich copolymers. 2,3,7,51 For such xMA/xMA and xMA/xA copolymerization systems, it is found that the effect of solvent choice on copolymer composition is small as long as the difference in monomer and solvent polarities is not large.…”
Section: Homopropagation Rate Coefficientsmentioning
confidence: 99%